Extra Domain B Fibronectin as a Target for Near-Infrared Fluorescence Imaging of Rheumatoid Arthritis Affected Joints In Vivo - Sonja Vollmer; Axel Vater; Kai Licha; Ines Gemeinhardt; Ole Gemeinhardt; Jan Voigt; Bernd Ebert; Jörg Schnorr; Matthias Taupitz; Rainer Macdonald; Michael Schirner (Molecular Imaging)
We investigated a molecular imaging approach for the detection of collagen-induced arthritis in rats by targeting the extra domain B (ED-B) of the extracellular matrix protein fibronectin. ED-B is a highly conserved domain (identical in human and rats) that is produced by alternative splicing during embryonic development and during vascular remodeling such as angiogenesis. The hallmark of rheumatoid arthritis is synovitis leading to both angiogenesis in the synovium and the promotion of cartilage and bone disruption. For in vivo diagnostics, the ED-B-binding single-chain antibody fragment AP39 was used as a targeting probe. It was covalently linked to the near-infrared dye tetrasulfocyanine (TSC) to be visualized by near-infrared fluorescence imaging. The resulting AP39-TSC conjugate was intravenously administered to rats with collagen-induced arthritis and the respective controls. Ovalbumin-TSC was used as control conjugate. Optical imaging over a time period of 24 hours using a planar imaging setup resulted in a clear enhancement of fluorescence intensity in joints with moderate to severe arthritis compared with control joints between 3 and 8 hours postinjection. Given that AP39 is a fully human antibody fragment, this molecular imaging approach for arthritis detection might be translated to humans.